Do Christians, Muslims, and Jews worship the same God? : four views /: four views. (2019) - Schwartz, Wm. Andrew; Cobb, John B; Beckwith, Francis; McDermott, Gerald R (Gerald Robert); Walls, Jerry L; Cumming, Joseph; Shenk, David W, 1937-
No abstract available